2021
DOI: 10.1021/acsomega.0c05532
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Micelle Formation on Surfactant Adsorption–Desorption

Abstract: The monomer−micelle equilibrium is shown to be responsible for an asymmetry between surfactant adsorption and desorption rates. When a solution containing micelles is brought into contact with a solid surface, the micelles dissociate to supply monomers that adsorb to the surface. When the same surface is subsequently exposed to a surfactant-free solution, desorption occurs slowly because of the higher affinity of the monomers to remain to the surface than to form micelles. As a result, the number of monomers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Complexation of divalent ions such as Ca 2+ and Mg 2+ lowers the viscosity of polymer solutions by introducing attractive polymer–polymer interactions and leads to precipitation at high concentrations. , Surfactants also tend to precipitate at high divalent ion concentrations, resulting in an increase in the interfacial tension . Divalent ions can also mediate the adsorption of anionic surfactants and polymers to negatively charged rock surfaces through a process called cation-bridging, resulting in higher concentrations required for chemical flooding. It is therefore highly important to measure the affinity of different chemicals to interact with divalent ions and determine the formation constants of their complexation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Complexation of divalent ions such as Ca 2+ and Mg 2+ lowers the viscosity of polymer solutions by introducing attractive polymer–polymer interactions and leads to precipitation at high concentrations. , Surfactants also tend to precipitate at high divalent ion concentrations, resulting in an increase in the interfacial tension . Divalent ions can also mediate the adsorption of anionic surfactants and polymers to negatively charged rock surfaces through a process called cation-bridging, resulting in higher concentrations required for chemical flooding. It is therefore highly important to measure the affinity of different chemicals to interact with divalent ions and determine the formation constants of their complexation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…From the voltammograms, it was noticed that with a volume of 100 μL of CTAB, the catalytic oxidation of DIU and DCN was higher than that of 50 μL; this can be ascribed to the uniform distribution of the CTAB over the electrode surface, leading to the reduction in the surface tension at the interface that contributes to an even analyte coverage over the electrode surface that improves the catalytic mechanism . Furthermore, an increase in the volume of CTAB (i.e., 150 and 200 μL) could direct the concentration saturation at the interface, which might be responsible for the asymmetry between the adsorption and desorption rates of the CTAB . In addition, the increase in the volume of CTAB drives the monomer–micelle equilibrium, which could decrease the analyte concentration over the electrode surface, possibly leading to a decreased intensity of the oxidation peak.…”
Section: Resultsmentioning
confidence: 99%
“…32 Furthermore, an increase in the volume of CTAB (i.e., 150 and 200 μL) could direct the concentration saturation at the interface, which might be responsible for the asymmetry between the adsorption and desorption rates of the CTAB. 33 In addition, the increase in the volume of CTAB drives the monomer− micelle equilibrium, which could decrease the analyte concentration over the electrode surface, possibly leading to a decreased intensity of the oxidation peak. The peak responses…”
Section: Probable Sensing Mechanism and Optimization Of Ctab Volumementioning
confidence: 99%
“…Second, when equilibrium reactions are used to describe surfactant adsorption, the surfactant desorbs completely from the rock surface when brine is injected, which is at odds with the experimental data. In a previous publication, we showed that the low desorption rate is a consequence of the monomer–micelle equilibrium, the low CMC value of the surfactant, and the low volume-to-surface ratio in the porous rock . Micellization was included in the reactive transport model by defining a micellization reaction with an equilibrium constant determined by the CMC value, which results in the correct behavior of the surfactant concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous publication, we showed that the low desorption rate is a consequence of the monomer−micelle equilibrium, the low CMC value of the surfactant, and the low volume-to-surface ratio in the porous rock. 32 Micellization was included in the reactive transport model by defining a micellization reaction with an equilibrium constant determined by the CMC value, which results in the correct behavior of the surfactant concentration. However, a proper match of the elemental concentrations has not yet been obtained and requires further work.…”
Section: ■ Results and Discussionmentioning
confidence: 99%